Strategi Mengajarkan Keterampilan Hidup Sehari-Hari Untuk Anak dan Remaja Dengan Retardasi Mental: Sebuah Review Literatur: LITERATUR REVIEW - sholihah, wiyanti maratus (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2021)
Abstract Educational programs for students with mental retardation emphasize the preparation of students to live independently after finishing school. One educational strategy for children and adolescents with mental retardation is to teach daily life skills. The purpose of this study is to conduct a literature review on strategies to teach daily life skills to children and adolescents with mental retardation. Literature searches were carried out on seven databases, namely ERIC, SpringerLink, ScienceDirect, SAGE, JSTOR, Emerald Insight and Google Schoolar. The keywords used in this search are "teaching daily living skills" and "mental retardation"; "Teaching daily living skills" and "intellectual disability". A total of 5 articles (N = 614) will be reviewed through a screening process based on inclusive and exclusive criteria. The results show that there are strategies to teach daily life skills to children and adolescents with mental retardation by using video prompting, video modeling, constant-time delay and most-to-least prompt. Keyword: daily living skills; mental retardation; video prompting; video modeling; constant-time delay; most-to-least prompt procedures; literature review